ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT INDOCEMENT TUNGGAL PRAKARSA Tbk. PERIODE TAHUN 2014-2018 - Yunarni, Baiq Reinelda Tri; Sudarta, Sudarta; Ramadhan, Johanandha Fandhy (Lembaga Penelitian dan Pendidikan Mandala, 2021)
The purpose of this study is to assess the financial performance of PT Indocement Tunggal Prakarsa Tbk in the period 2014 to 2018. The success of a company in achieving its goals and meeting the needs of the community is very dependent on company performance. One way to measure or evaluate performance is to analyze financial statements.This study uses a descriptive research method with a quantituve approach that is analysus based on data calculations. The data used in this study are secondary data in the form of financial statements for the period 2014 to 2018, using the calculation of liquidity ratios, solvency, activity, and profitability.The result of this study indicate that PT Indocement Tunggal Prakarsa Tbk is in a liquid state when viewed from the liquidity ratio because the current ratio and quick ratio are above the industry standard. Judging from the solvency ratio, the financial performance of PT Indocement Tunggal Prakarsa Tbk can be said to be solvable because in terms of the debt to equity ratio, and the debt to asset ratio is below the industry standard. But the financial performance of PT Indocement Tunggal Prakarsa Tbk when viewed from the activity ratio (receivable turnover ratio, inventory turnover ratio, working capital turnover ratio, fixed assets turnover ratio, and total asset turnover ratio) and profitability ratio (net profit margin, return on investment, and return on equity) is not optimal because the company’s profit continue to fall and ineffectiveness of the company in utilizing its assets.